Factors Affecting The Selection Of Student Career As A Public Accountant - Merry Susanti; Sofia Prima Dewi; Sufiyati Sufiyati (Jurnal Akuntansi, 2019)
The purpose of this study is to determine factors that influence the selection of student career as a public accountant. The data collection method was conducted by distributing questionnaires to Universitas Tarumanagara students. The questionnaire distributed from August to October 2018. Data processing methods were carried out by using partial least square-structural equation modeling (PLS-SEM), which is the contribution of our research, whereas previous research used SPSS as their statistic tool. We also added the motivation variable that not used in the research that we replicate. The data is first tested for its validity and reliability followed by the multicollinearity test, F2 test, adjusted R2, and finally the t test. Â The results showed that only financial rewards had a positive influence on the selection of student career as public accountants while professional training, professional recognition, social values, work environment, labor market considerations, personality, and self-motivation had no influence.